2011
DOI: 10.14358/pers.77.10.1011
|View full text |Cite
|
Sign up to set email alerts
|

Building Extraction and Rubble Mapping for City Port-au-Prince Post-2010 Earthquake with GeoEye-1 Imagery and Lidar Data

Abstract: This paper uses GeoEye-1 imagery and airborne lidar (Light Detection and Ranging) data to map buildings and their rubble in Port-au-Prince caused by the Haiti earthquake on 12 January 2010. This is achieved by performing an objectbased one-class-at-a-time land cover classification of the image and lidar data using spectral, textural and height information. Classification accuracy is about 87 percent overall, and approximately 80 percent for buildings and rubble. Comparison of manually-selected 200 actual damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…It is prone to being correctly classified for concrete buildings having very prominent collapse or damage structures with totally broken down roofs. Steel or wooden frame buildings with metal sheet roofs, where the building was physically collapsed but there was no visible deformation or textural change to its roof structure, would be hard to correctly classify [63], which would decrease the number of correctly classified collapsed buildings. The Kappa value for test A (37.7%) and test B (45.6%) also indicated that SqueezeNet performed better on test B to discriminate collapsed buildings, which could be partly caused by the difference in building structures in these two regions.…”
Section: Identifying Collapsed Buildings Using Cnnsmentioning
confidence: 99%
“…It is prone to being correctly classified for concrete buildings having very prominent collapse or damage structures with totally broken down roofs. Steel or wooden frame buildings with metal sheet roofs, where the building was physically collapsed but there was no visible deformation or textural change to its roof structure, would be hard to correctly classify [63], which would decrease the number of correctly classified collapsed buildings. The Kappa value for test A (37.7%) and test B (45.6%) also indicated that SqueezeNet performed better on test B to discriminate collapsed buildings, which could be partly caused by the difference in building structures in these two regions.…”
Section: Identifying Collapsed Buildings Using Cnnsmentioning
confidence: 99%
“…More than 180 government buildings also collapsed, including 87% of key offices (DesRoches et al ., ). The majority of the buildings that collapsed were made of lightly reinforced concrete frames filled with concrete masonry (EERI, ; Fierro and Perry, ; Ural et al ., ) and, as a result, the bulk of the waste produced took the form of rubble derived from these materials. The nature of the rubble generated in Haiti had important implications for its clearance.…”
Section: Post‐disaster Rubble Clearance: Context and Haitian Experiencementioning
confidence: 99%
“…Producing damage maps using experts after disasters in a manual manner proves our claim. To the best of our knowledge, in the damage detection application, the fuzzy-based decision making systems can be used for two main procedures including: (1) land use/cover classification [29,30] and (2) modeling the damage extent of buildings from the extracted features [2,13]. Ural et al (2011) employed a fuzzy classifier in order to map buildings and their rubble after the 2010 Haiti earthquake in a robust manner [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Undefined values of variables are corrected using Equations (24) and (25). Finally, using Equations (15) to (20), costs of the new children are calculated and inserted into Equation (30).…”
Section: Stage 3: Decision Makingmentioning
confidence: 99%